2023
DOI: 10.3892/ijo.2023.5490
|View full text |Cite
|
Sign up to set email alerts
|

High‑throughput screening identification of a small‑molecule compound that induces ferroptosis and attenuates the invasion and migration of hepatocellular carcinoma cells by targeting the STAT3/GPX4 axis

Abstract: Hepatocellular carcinoma (HCC) is a lethal malignancy. Although considerable efforts have been made in recent years regarding treatments, effective therapeutic drugs for HCC remain insufficient. In the present study, polyphyllin VI was identified as a potential therapeutic drug for HCC by screening natural herbal compounds. The therapeutic effects of polyphyllin VI were assessed using Cell Counting Kit-8, lactate dehydrogenase release and colony formation assays. The occurrence of ferroptosis was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Ferroptosis plays a pivotal role in regulating the initiation, invasion, and metastasis of multiple cancers [ 32 , 33 ]. To explore whether LASS2 suppresses tumour cell growth and metastasis through the ferroptosis signalling pathway, the CCK-8 assays, transwell migration and Matrigel invasion assays were performed on multiple tumour cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis plays a pivotal role in regulating the initiation, invasion, and metastasis of multiple cancers [ 32 , 33 ]. To explore whether LASS2 suppresses tumour cell growth and metastasis through the ferroptosis signalling pathway, the CCK-8 assays, transwell migration and Matrigel invasion assays were performed on multiple tumour cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there is no report of PPVII‐induced ferroptosis. Recently, Huang et al reported that polyphyllin VI of pennogenins induced ferroptosis in the System XC − pathway of hepatocellular carcinoma cells by targeting STAT3 (Huang et al, 2023). In this study, we report that PPVII acts as a direct inhibitor of TOPK to activate autophagy‐dependent iron metabolism‐associated ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 535 HCC Polyphyllin VI Phosphorylation STAT3 Polyphyllin VI induces the ferroptosis through inhibiting STAT3 phosphorylation, which inhibits GPX4 expression. 536 HCC Anisomycin Phosphorylation p38MAPK Anisomycin activates p38MAPK to induce ferritinophagy through the phosphorylation of histone H3 on serine 10 (p-H3S10). 537 NSCLC Bufotalin Ubiquitination GPX4 Bufotalin induces ferroptosis by facilitating the ubiquitination and degradation of GPX4.…”
Section: Modulation Of Epigenetic and Posttranslational Modifications...mentioning
confidence: 99%
“… 535 Polyphyllin VI induces ferroptosis by inhibiting STAT3 phosphorylation, which inhibits GPX4 expression in HCC. 536 Anisomycin activates p38MAPK to induce ferritinophagy through the phosphorylation of histone H3 on serine 10 (p-H3S10) in HCC. 537 …”
Section: Modulation Of Epigenetic and Posttranslational Modifications...mentioning
confidence: 99%